Effects of receptor dimerization on the interaction between the class I major histocompatibility complex-related Fc receptor and IgG. - Raghavan, M (1995)
The neonatal Fc receptor (FcRn) transports maternal IgG from ingested milk in the gut to the bloodstream of newborn mammals. An FcRn dimer was observed in crystals of the receptor alone and of an FcRn-Fc complex, but its biological relevance was unknown. Here we use surface plasmon resonance-based biosensor assays to assess the role of FcRn dimerization in IgG binding. We find high-affinity IgG binding when FcRn is immobilized on a biosensor chip in an orientation facilitating dimerization but not when its orientation disrupts dimerization. This result supports a model in which IgG-induced dimerization of FcRn is relevant for signaling the cell to initiate endocytosis of the IgG-FcRn complex.